Insulin resistance: from the source of development to clinical consequences - Waldemar Pluta; Wioleta Dudzińska; Anna Lubkowska (Kazimierz Wielki University, 2020)
Insulin resistance is a disorder of glucose homeostasis, which is a decrease in tissue sensitivity to insulin despite normal or elevated serum hormone levels. The main sources of development are genetic and environmental factors, including excessive consumption of fats, simple sugars and high-calorie foods, and lack of physical activity. One of the most objective methods of assessing insulin resistance is the HOMA-IR index calculated on the basis of glucose and insulin levels in the blood. Among the clinical consequences, type 2 diabetes and polycystic ovary syndrome play the most important role. The goal of treatment is not only to reduce insulin resistance, but also to protect pancreatic β cells.